The Professional and Academic Literature Review: A Framework for Retention Strategies Adopted by Bank Managers - El Alam, Younes; Belkasseh, Mohammed (Archives of Business Research, 2023)
Banks’ implementation of managerial strategies motivating teams and addressing employees’ needs tends to lower their organization turnover. Certain bank human resource managers are challenged with finding processes for the purpose of lowering the turnover rate. The academic study of employee retention has identified some constant elements that retain workers with the same organization throughout time. The purpose of this study is to inquire into the methods utilized by banking executives to keep their best workers on board. In this paper, the author will discuss, through the existing academic literature, the framework for the topic of employee turnover by conducting a comprehensive review. The key words we searched for in the literature include job satisfaction, job dissatisfaction, motivation theories, extrinsic and intrinsic factors, skilled human resource management, the difficulties of retaining key employees, effective methods for doing so, employee attrition, and Herzberg’s two-factor theory. Four major themes were discussed in the literature review, supported by the motivation (intrinsic factors)-hygiene (extrinsic factors) theory, comprising: conceptual frameworks, what drives people to work, what keeps them there, and how to reduce staff turnover.